1997
DOI: 10.1111/j.0022-3646.1997.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

PATTERNS OF REPRODUCTION, GENETIC DIVERSITY, AND GENETIC DIFFERENTIATION IN CALIFORNIA POPULATIONS OF THE GENICULATE CORALLINE ALGA LITHOTHRIX ASPERGILLUM (RHODOPHYTA)1

Abstract: The reproductive composition and genetic diversity of populations of the red seaweed Lithothrix aspergillurn Gray (0. Corallinales) were studied at three southern California sites (Shaw's Cove and Treasure Island, Laguna Beach; Indian Rock, Santa Catalina Island) and at a fourth site (Bodega Bay) located in northern Calijimia. Sexually reproducing populations were conjined to southern California. Diploid individuals were numen'cally dominant over haploid (gametophytic) individuals at all sites. Intertidal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
3
12
0
Order By: Relevance
“…Such conditions include fragmented (Adjeroud et al., ) and marginal habitats (Baums et al., ), high disturbance frequency (Foster et al., ) or high stress related to human activities (Oliva et al., ). Many coral reef organisms can reproduce through both sexual and asexual reproduction, such as scleractinian corals (Harrison, ), hydrocorals (Lewis, ), coralline algae (Pearson & Murray, ) and sponges (Whalan, Johnson, Harvey, & Battershill, ). Environmental conditions vary greatly among coral reef habitats (e.g., temperature (Glynn, ), light (Vermeij & Bak, ), water flow (Monismith, ) and water quality conditions (Fabricius, )), and these conditions can impose divergent selection pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Such conditions include fragmented (Adjeroud et al., ) and marginal habitats (Baums et al., ), high disturbance frequency (Foster et al., ) or high stress related to human activities (Oliva et al., ). Many coral reef organisms can reproduce through both sexual and asexual reproduction, such as scleractinian corals (Harrison, ), hydrocorals (Lewis, ), coralline algae (Pearson & Murray, ) and sponges (Whalan, Johnson, Harvey, & Battershill, ). Environmental conditions vary greatly among coral reef habitats (e.g., temperature (Glynn, ), light (Vermeij & Bak, ), water flow (Monismith, ) and water quality conditions (Fabricius, )), and these conditions can impose divergent selection pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Population differentiation has also been shown at scales of tens to hundreds of kilometres (e.g. Intasuwan et ai., 1993;Lu & Williams, 1994;Williams & Oi Fiori, 1996;Benzie et ai., 1997;Pearson & Murray, 1997;Sosa et al, 1996Sosa et al, , 199816 Kusumo & Oruehl, 2000) but only two studies we are aware of have explicitly tested for isolation by distance. Engel et al (1997) found a significant effect of isolation by distance in ten Graciiaria gracilis populations along the French coast (0-1000 km).…”
Section: Introductionmentioning
confidence: 99%
“…But the absence of sexual fusion in the laboratory is not an absolute evidence of asexual populations, for gametogenesis might be missed owing to transient sexual reproduction or unfavourable conditions (Clayton, 1976(Clayton, , 1978(Clayton, , 1980Pedersen et al, 1987). Genetic population analysis facilitates their identification because genetic differences are expected between sexual and asexual populations (Innes and Yarish, 1984;Pearson and Murray, 1997;Kogame et al, 2005). So the present study only confirmed that there are sexual erect thalli of S. lomentaria in Dalian waters and the existence of the asexual erect thalli of S. lomentaria in this region needs further investigation.…”
Section: Discussionmentioning
confidence: 52%